Using systems approaches to understand women's conservation leadership and urban residents' wildscape behavior - Jones, Megan Siobhán, author; Solomon, Jennifer, advisor; Teel, Tara L., advisor; Gavin, Michael, committee member; Martinez, Doreen E., committee member (Colorado State University. Libraries, 2020)
This dissertation seeks to investigate a fundamental question in the field of conservation science: How do we build and sustain capacity for conservation leadership and action to protect biodiversity in a changing world? Worldwide, conservation practitioners seek to make conservation accessible to more people embedded in highly variable social-ecological contexts, but their efforts are often hindered by the characteristics of the systems (e.g. communities, institutions) they are embedded within. Fulfilling the aspirations of conservation will require broader participation from a greater diversity and number of conservation actors. Achieving this expansion of the conservation community will depend on our ability to understand how individuals' actions and leadership are nested within the broader systems that these individuals respond to and seek to reshape. In the three studies of this dissertation I therefore seek to understand the behavior and motivations of conservation leaders and actors through a systems approach, by investigating the experiences of different groups of practitioners who challenge and reconfigure the inherited model of how conservation occurs. In my first two research studies I explore the experiences of women, one of many groups that have historically been excluded from and marginalized in leadership positions. Specifically, I investigate women conservation leaders' perceptions of professional gender-related and motherhood-related challenges and supports. In Chapter 2 I find that women in conservation leadership in the United States experience at least six categories of gender-related challenges over their careers, which fall more heavily on different women based on race, ethnicity, age, and seniority. I find further that women navigate those challenges with the help of structural and relational supports. In Chapter 3 I examine how the intersection of motherhood and conservation leadership creates a series of choices for individual women, and that these choices are constrained or enabled by the families, organizations, and profession within which they work and live. In my final research study, reported in Chapter 4, I investigate the factors motivating urban residents who are expanding the scope of conservation leadership through voluntary engagement in and advocacy for wildscape gardening on their properties and in their communities. I determine that residents participating in an urban conservation program engage in many different, interconnected wildscaping behaviors, and are motivated to do so by a variety of individual and collective factors. My findings further suggest that these factors change over time in response to feedbacks from the impacts that wildscape gardeners' actions have on a complex multilevel social-ecological system. The findings from these studies shed light on how conservation can benefit from systems approaches to become a more sustainable and inclusive movement in different contexts, so as to better fulfill its vision of protecting equitable, biodiverse social-ecological systems.
Keywords: mixed methods research; pro-environmental behavior; women's leadership; motherhood; intersectionality; social-ecological systems